FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMINATAN KONTRASEPSI PIL DAN SUNTIK DI WILAYAH KERJA PUSKESMAS GLOBAL TIBAWA - Melisa R Baharu; Harismayanti Harismayanti; Andi Kurniati Naue (Akademika, 2019)
The purpose of this research is to know how factors (age, knowledge, and number of child ren) can influence contracepti on specialization , this research use analytical survey method with cross sectional approach. Conducted in global public health center of Tibawa Gorontalo Regency with the number of samples of 63 respondents taken using Purposive Sampling technique. Data analysis using chi - square statistic test with degree of significance 0,05. The result of the research showed that there was a significant correlation between age factor with the pillandinjection contraception specialization (P value 0.007